Postglacial Vegetational History of the Eastern Avalon Peninsula, Newfoundland, and Holocene Climatic Change Along the Eastern Canadian Seaboard - Brown Macpherson, Joyce (Géographie physique et Quaternaire, 1982)
ABSTRACTTwo radiocarbon-dated pollen profiles from the eastern Avalon Peninsula suggest late déglaciation (probably no earlier than 9700 BP at the coast), followed by a brief period of tundra vegetation. After 9300 BP a rich shrub tundra at lower elevations was invaded by spruce, balsam fir and tree birch until at ca 8400 BP the vegetation was an open woodland. The forest remained open for the next 3000 years; evidence of fire and the continuous presence of Populus suggest drier and warmer conditions than at present. The period of maximum warmth, ca 5400-3200 BP, saw the closing of the forest cover, a rise in the level of the tree limit in the interior upland and an increase in precipitation. After 3200 BP decreasing temperatures resulted in a lowering of the tree limit. The climatic changes inferred for the Avalon Peninsula are compared with those inferred from palaeo-environmental studies along the eastern North American seaboard from Baffin Island to New England. A sequence of changing controls on the regional atmospheric circulation during the Holocene is suggested.